On the Spaces of λ-Convergent and Bounded Sequences: M. Mursaleen, Abdullah K. Noman - Team, Support (Thai Journal of Mathematics, 2010)
In the present paper, we introduce the notion of λ-convergent and bounded sequences. Further, we define some related BK spaces and construct their bases. Moreover, we establish some inclusion relations concerning with those spaces and determine their α-, β- and γ-duals. Finally, we characterize some related matrix classes.